CRM, SOCIAL NETWORKS AND SMALL AND MEDIUM ENTERPRISES. DOES IT ALL FIT TOGETHER? - Kantorová Kateřina; Bachmann Pavel; Hrdinková Monika (Univerzita sv. Cyrila a Metoda v Trnave, 2015)
The original concept of customer relationship management as based on communication in the physical environment is gradually transforming into a new kind of marketing approach where contact through social networks and relationships within online communities predominate. This paper aims to increase knowledge of the use of customer relationship management and social customer relationship management practices in small and medium enterprises conducting their business in the Czech Republic. A sample of 308 respondents, primarily small and medium enterprises managers, employees and marketing specialists was collected using a questionnaire. The findings showed that organizations perceive digital marketing as more important than traditional marketing. About two-thirds of respondents consider customer relationship orientation to be very important; however, Social customer relationship management consider as “very important” about 15% of respondents. The comparison of findings to international studies and to larger corporations has brought some interesting knowledge.
CRM, sociální sítě malých a středních firem. Jak to všechno do sebe zapadá?
Keywords: Customer Relationship Management, Social CRM, Small and medium enterprise, Social Networks, Czech Republic; CRM, sociální CRM, malé a střední podnikání, sociální sítě, Česká republika